EFFECT OF HARVESTING AND DESICCATION METHODS ON QUALITY OF OIL FLAX PRODUCTS AND ECONOMIC EFFICIENCY OF THE CROP IN CASE OF ITS USE BOTH FOR SEED AND FIBRE - Viktor GARMASHOV; Viktor SHCHERBAKOV; Inna KOGUT; Pavlo LYKHOVYD; Oleksandr RUDIK; Ali KERIMOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This research is aiming at exploration of some factors, influencing production cost of cow milk in Bulgarian dairy farms. Seventeen dairy cattle farmers in Bulgaria were enquired. Pearson correlation coefficients between the following variables were calculated and analyzed: cow number, average milk yield, clinical mastitis, calves' mortality up to 6 months of age, endometritis, expenses for medications per 1 cow, cows per 1 worker, and production cost per 1liter milk. Also a regression model with an application of the Ordinary Least Squares Method was developed. The model has the represented form: Pc = c + c1.Cw + c2.My + c3.Em + u, where: Pc – natural logarithm of the production cost per 1 liter of milk; Cw – natural logarithm of cows per 1 worker; My – natural logarithm of average milk yield; Em - natural logarithm of expenses for medications per 1 cow; c1, c2 and c3 – coefficients in front of the regressors; c – constant; u - error of the regression. Growth in clinical mastitis leads to drop down of milk yield while the medication expenses per cow become larger. Medication expenses per 1 cow also increment with the rise of calves' mortality and endometritis. The production cost is influenced significantly from the cows’ number per worker and average milk yield: with the increment of one of them, a decline in production cost per liter is observed.